EVALUATION OF HERBAL MEDICINES AND ANIMAL EXPERIMENTATION - Sitohang, Nadiyah Safitri; Sabrina, Nur Nabila; Ferizon, Ayla Fenezza; Raffi Arrasyid, Muhammad; Adenina, Syarinta (International Journal of Islamic and Complementary Medicine, 2024)
Over time, the use of herbal medicines has increased rapidly. This is influenced by several main factors, including the relatively cheap price and avoiding concerns about the side effects of chemical drugs. In practice, screening tests need to be carried out on a drug product that will be marketed, one of which is through a toxicity test. The use of animal models as experimental materials provides invaluable information in many aspects of pathophysiology, treatment, and diagnosis of human disease. Without exception, research on traditional ingredients also relies heavily on animals in in vivo, in situ, and in vitro experiments. This study uses a literature review with a descriptive approach based on secondary literature derived from Google Scholar, PubMed, and Science Direct. Research conducted on animals regarding herbal medicine can provide valuable insights into a herbal remedy. Selecting the appropriate animal for a study is crucial to obtain scientifically convincing results. Animals used for pharmacological studies should be standard species. Rodents, guinea pigs, rabbits, cats, and dogs are often used in traditional herbal medicine research. Moreover, herbal materials used for pharmacological research should be standardized to control quality and ensure the reproducibility of experimental outcomes. The standardization of herbal medicine should encompass species identification (name, origin, description, and purity), extraction procedures, chemical analysis of major and bioactive compounds, heavy metals, pesticides, and storage stability.